THE INFLUENCE OF WORK LIFE BALANCE AND WORK ENVIRONMENT ON ASSISTANT STORE LEADER PERFORMANCE WITH WORK MOTIVATION AT SUPER INDO SURABAYA - Elysabet Nora; Akhmad Fauzi; Tri Kartika Pertiwi (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of work life balance and work environment on employee performance with work motivation as an intervening variable on assistant store leader level employees at Super Indo Surabaya. The material of this study is based on the problem of dual roles carried out by ASL, namely as a team leader and technical implementer, where this has the potential to disrupt the balance between work and personal life, or what is known as work life balance. Work environment problems that require improvement and procurement of supporting equipment for workers to facilitate employees in doing their work optimally. The research method used is quantitative. The sample in this study was 75 assistant store leader level employees at Super Indo Surabaya. The data analysis technique used partial least square (PLS). The results showed that work life balance and work environment had a positive and significant effect on employee performance. Work life balance affects employee performance through work motivation but work motivation is not proven significantly as an intervening variable between the work environment and employee performance.